1.W załączniku
2.
[tex]1+ctg^2x=\frac{1}{sin^2x}[/tex]
[tex]L=1+ctg^2x=1+\frac{cos^2x}{sin^2x}=\frac{sin^2x}{sin^2x}+\frac{cos^2x}{sin^2x}=[/tex]
[tex]\frac{sin^2x+cos^2x}{sin^2x}=\frac{1}{sin^2x}=P[/tex]
3.
a)
[tex]1 - 2sin x cos x = (sin x - cos x)^2[/tex]
[tex]L=1 - 2sin x cos x =sin^2x-2 sinx cos x+cox^2x=(sin x - cos x)^2=P[/tex]
b)
[tex]2 sin^2 x- 1 = 1 - 2 cos^2 x[/tex]
[tex]L=2 sin^2 x- 1=2(1-cos^2x)-1=2-2cos^2x-1=1 - 2 cos^2 x=P[/tex]
c)
[tex]cos^2 x + tg^2 x cos^2 x = 1[/tex]
[tex]L=cos^2 x + tg^2 x= cos^2 x + \frac{sin^2x}{cos^2x}\cdot cos^2 x=cos^2x+sin^2x=1=P[/tex]